O violoncelo na obra de Marlos Nobre: um estudo sobre o Desafio II e Três cantos de Iemanjá - Rafael Gaspar Anastácio (2019)
This work aims to analyze two pieces for cello by the Brazilian composer Marlos Nobre – Desafio II and Três Cantos de Iemanjá – seeking support for the interpretation and identifying the main technical and stylistic aspects of the composer 's cello writing. The study has as justification the relevance of the works for the contemporary national music scene and for the cello repertoire because of its musical and technical richness. Thusly the research attempts to encourage the insertion of works in the repertoire of professional and students cellists, valuing Brazilian compositional production for the instrument. In addition, it aims to provide greater visibility to the work of the composer Marlos Nobre and encourage the musical and academic study focused on the Brazilian repertoire.